Pemaknaan Hadis secara Haqiqi dan Majazi: Telaah Hadis Tentang Akhir Kenabian - Sonhaji, Siti Qurrotul Aini (Advances in Humanities and Contemporary Studies, 2022)
Hadith must be believed to be true as religious text and linguistic text which always present the infinite meanings corresponds the point of view of each reviewer makes hadith interesting to be studied. In studying  Hadith about the end of this prophethood, the author uses Hadith understanding method of Syuhudi Ismail, which in understanding Hadith requires an approach to the science of hadith, language and history. The meaning of the word khātim in the hadith narrated by Abu Hurairah (وَأَنَا اتَمُ النَّبِيِّين) and in Surah al-Ahzab : 40 (وَلَكِنْ لَ اللَّهِ وَخَاتَمَ النَّبِيِّينَ), comes from the root word kha-ta-ma which means a-ba-'a (closing on something in order it can be entered by something else). The presence of Prophet Muhammad SAW is a sign of the 'end' or 'ultimate' of Allah's words perfection. Muhammad Iqbal in his book tajdīd al-tafkīr al-dīnī fī al-islām says that with the end of prophetic period, a new era has emerged, it is the period of mind. The word 'end' means openness for everyone to seek the truth freely without being fixated on one person or figures. From this research, it can be understood that practicing Hadith is not only in the form of behavior and speech, but also in the form of meanings as an effort to discuss the Hadith properly so it can be understood along with the limitations of space and time.Keyword: Hadith, Khātim, Hadith understanding method